Evaluation of patients with abnormalities on intraoperative cholangiogram: time to abandon endoscopic retrograde cholangiopancreatography as the initial follow-up study. Issue 2 (16th June 2015) - Bill, Jason G; Kushnir, Vladimir M; Mullady, Daniel K; Murad, Faris M; Azar, Riad R; Easler, Jeffery J; Early, Dayna S; Edmundowicz, Steven A
Abstract : Background: Endoscopic retrograde cholangiopancreatography (ERCP) is currently the method of choice for the postoperative evaluation of suspected bile duct stones seen on intraoperative cholangiogram (IOC); however, the sensitivity of IOC for identifying biliary pathology is unclear, with studies reporting false positive rates between 30% and 60%. Objective: Evaluate the sensitivity of IOC for biliary pathology, using ERCP with sphincterotomy and balloon sweep as gold standard. Design: Retrospective cohort study. Setting: Tertiary medical centre. Patients: 130 consecutive patients (age 51.3±1.7 years, 69.2% women) who underwent ERCP for the evaluation of abnormalities identified on IOC between 2005 and 2013. Interventions: Endoscopic retrograde cholangiopancreatography Main outcome measurements: Sensitivity of IOC, identify predictors of positive postoperative ERCP and ERCP-related complications. Results: ERCP was successful in all 130 subjects. ERCP-related adverse events occurred in six (4.3%) patients, including self-limited post-sphincterotomy bleeding in three (2.3%) and mild post-ERCP pancreatitis in three (2.3%). Overall, 41 (31.5%) patients had normal cholangiogram at time of ERCP. Finding of a filling defect on IOC was the only predictor for the presence of common bile duct stones on postoperative ERCP (OR 3.3, 95% CI 1.0 to 10.8, p=0.05). Limitations: Retrospective study design. Conclusions: Nearly one-third of patients with abnormal IOC had a normal postoperative ERCP. Significant pathology could have been missed in 1/130 patients. Based on these findings, we believe the use of less-invasive diagnostic modalities may be used in place of ERCP in patients with suspected choledocholithiasis on IOC.